Ras GTPase-Activating Protein Regulation of Actin Cytoskeleton and Hyphal Polarity in Aspergillus nidulans - Harispe, Laura (American Society for Microbiology (ASM), 2008)
Aspergillus nidulans gapA1, a mutation leading to compact, fluffy colonies and delayed polarity establishment, maps to a gene encoding a Ras GTPase-activating protein. Domain organization and phylogenetic analyses strongly indicate that GapA regulates one or more “true” Ras proteins. A gapAΔ strain is viable. gapA colonies are more compact than gapA1 colonies and show reduced conidiation. gapAΔ strains have abnormal conidiophores, characterized by the absence of one of the two layers of sterigmata seen in the wild type. gapA transcript levels are very low in conidia but increase during germination and reach their maximum at a time coincident with germ tube emergence. Elevated levels persist in hyphae. In germinating conidiospores, gapAΔ disrupts the normal coupling of isotropic growth, polarity establishment, and mitosis, resulting in a highly heterogeneous cell population, including malformed germlings and a class of giant cells with no germ tubes and a multitude of nuclei. Unlike wild-type conidia, gapAΔ conidia germinate without a carbon source. Giant multinucleated spores and carbon source-independent germination have been reported in strains carrying a rasA dominant active allele, indicating that GapA downregulates RasA. gapAΔ cells show a polarity maintenance defect characterized by apical swelling and subapical branching. The strongly polarized wild-type F-actin distribution is lost in gapAΔ cells. As GapA-green fluorescent protein shows cortical localization with strong predominance at the hyphal tips, we propose that GapA-mediated downregulation of Ras signaling at the plasma membrane of these tips is involved in the polarization of the actin cytoskeleton that is required for hyphal growth and, possibly, for asexual morphogenesis.